EFISIENSI PENULARAN VIRUS MOSAIK BENGKUANG DENGAN Aphis craccivora Koch. DAN A. gossypii Glover. - Tri Asmira Damayanti; Endah Muliarti; Dewi Sartiami (Universitas Trunojoyo Madura, 2010)
Yambean mosaic virus is the most important virus infecting yam bean in Indonesia. The virus were transmitted either mechanically or via aphid. This study to test the transmission efficiency of the virus via A. craccivora and A. gossypii by using different number of aphid such 1, 3, 5, 7, and 10 for each treatment. To determine the transmission efficiency, incubation period, type of symptom and incidence were used as parameter. Transmission of virus by A. craccivora showed incidence range 90 to 100%, significant differences in incubation time of 1 aphid compared to other treatments and showed severe leaf mosaic, vein-banding and severe leaf malformation such as string. However, the incidence of transmission of virus by A. gossypii was range 70 to 100%, with longer incubation period in compare with A. craccivora. There was no significant differences of incubation period among treatments by A. gossypii. The infected plants showed leaf malformation, vein-banding, wrinkle and blotch on the leaves. Based on these, both aphids species could transmitted virus efficiently, and among them A. craccivora considerate has higher ability as efficient insect vector to transmit the virus in compare with A. gossypii.